Correlation of protection against Japanese encephalitis virus and JE vaccine (IXIARO ®) induced neutralizing antibody titers - Van Gessel, Yvonne; Klade, Christoph S.; Putnak, Robert; Formica, Alessandra; Krasaesub, Somporn; Spruth, Martin; Cena, Bruno; Tungtaeng, Anchalee; Gettayacamin, Montip; Dewasthaly, Shailesh (Vaccine, 2011)
Immune sera from volunteers vaccinated in a blinded Phase 3 clinical trial with JE-VAX ® and a new Japanese encephalitis virus (JEV) vaccine (IC51 or IXIARO), were tested for the ability to protect mice against lethal JEV challenge. Sera from IXIARO vaccinated subjects were pooled into four batches based on neutralizing antibody measured by plaque reduction neutralization test (PRNT 50 titer): high (∼200), medium (∼40–50), low (∼20) and negative (<10). Pooled sera from JE-VAX ® vaccinated subjects (PRNT 50 titer ∼ 55) and pooled JEV antibody negative pre-vaccination sera were used as controls. Groups of ten 6- to 7-week-old female ICR mice were injected intraperitoneally with 0.5 ml of each serum pool diluted 1:2 or 1:10, challenged approximately 18 h later with a lethal dose of either JEV strain SA14 (genotype III) or strain KE-093 (genotype I) and observed for 21 days. All mice in the non-immune serum groups developed clinical signs consistent with JEV infection or died, whereas high titer sera from both IXIARO and JE-VAX ® sera protected 90–100% of the animals. Statistical tests showed similar protection against both JEV strains SA14 and KE-093 and protection correlated with the anti-JEV antibody titer of IXIARO sera as measured by PRNT 50. Ex vivo neutralizing antibody titers showed that almost all mice with a titer of 10 or greater were fully protected. In a separate study, analysis of geometric mean titers (GMTs) of the groups of mice vaccinated with different doses of IXIARO and challenged with JEV SA14 provided additional evidence that titers ≥ 10 were protective.